¿Cómo impulsar una sociedad científica de estudiantes de medicina? - Quispe-Juli, Cender Udai (2019)
Abstract In recent decades the student undergraduate research initiatives have increased; so the scientific societies of medical students have an increasingly important role in the development of research in Latin America. The growth and consolidation of these organizations depends on strengthening its technical capabilities, organizational skills and leadership. The basic strategies to improve the organization are: Establish permanent training programs in research knowledge; implement journal clubs; encourage self-learning and use of the various resources offered by web 2.0; training in management and administration; standardize processes and procedures; establish partnerships with other institutions; promote the exchange of experiences with similar organizations.